1972
DOI: 10.1007/bf00439375
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic effects of ?9-tetrahydrocannabinol on variable interval schedule performance in rats

Abstract: Abstract. Four rats were trained to barpress for water reinforcement under a variable interval 60 sec schedule. 1XTine acute administrations of (--)Ag-trans-tetrahydrocannabinol, in amounts ranging from 0.25 to 16.0 mg/kg, produced doserelated effects on responding; overall response rate increased at lower doses, while higher doses produced ataxia and a complete suppression of responding. Increased response rates reflected changes both in response spacing and in the lengths of postreinforcement pauses. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…In acute regimes, ∆ 9 -THC showed a biphasic response with increasing hyperactivity succeeded by suppression of activity as the dose increased. These findings are consistent with studies in rodents which reported a stimulation of locomotor activity by ∆ 9 -THC at low concentrations, and suppression at higher concentrations (Grisham and Ferraro 1972, Ferraro and Gluck 1974, Taylor and Fennessy 1977. A recent study (Freedland et al 2002) suggested that high concentrations of ∆ 9 -THC in adult rats decreased cerebral metabolism.…”
Section: Discussionsupporting
confidence: 86%
“…In acute regimes, ∆ 9 -THC showed a biphasic response with increasing hyperactivity succeeded by suppression of activity as the dose increased. These findings are consistent with studies in rodents which reported a stimulation of locomotor activity by ∆ 9 -THC at low concentrations, and suppression at higher concentrations (Grisham and Ferraro 1972, Ferraro and Gluck 1974, Taylor and Fennessy 1977. A recent study (Freedland et al 2002) suggested that high concentrations of ∆ 9 -THC in adult rats decreased cerebral metabolism.…”
Section: Discussionsupporting
confidence: 86%
“…As shown in Figure , both phytocannabinoids show very similar triphasic dose–response curves with two apparent peaks in efficacy, one within a dose range of 1.0–2.5 mg·kg −1 and the other within the 10–20 mg·kg −1 range. Biphasic effects of cannabinoids have been reported (Grisham and Ferraro, ; Kwiatkowska et al, ; Margulies and Hammer, ), and one study has reported triphasic effects of THC on locomotor activity across a wide range of doses (Sanudo‐Pena et al, ). In female mice dosed daily with CBD for 14 days, paclitaxel‐induced mechanical sensitivity was attenuated at the 10 mg·kg −1 dose but not the 5.0 mg·kg −1 dose (Ward et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, with both FI (Brady & Balster, 1980;Elsmore & Manning, 1974;Stark & Dews, 1980) and VI schedules (Elsmore & Manning, 1974;Ferraro & Gluck, 1974;Grisham & Ferraro, 1972), low doses of marijuana increased response rates. Yet moderate doses of marijuana have no effect on the temporal distribution of responses on FI schedules (Frankenheim, McMillan, & Harris, 1971).…”
Section: Discussionmentioning
confidence: 99%